Simultaneous Discrimination of Cys/Hcy and GSH With Simple Fluorescent Probe Under a Single-Wavelength Excitation and its Application in Living Cells, Tumor Tissues, and Zebrafish - Yan, Dongling; Liu, Likun; Liu, Xiangbao; Liu, Qi; Hou, Peng; Wang, Hao; Xia, Chunhui; Li, Gang; Ma, Chunhui; Chen, Song (Frontiers in Chemistry, 2022)
Owing to the important physiological sits of biothiols (Cys, Hcy, and GSH), developing the accurate detection methods capable of qualitative and quantitative analysis of biothiols in living systems is needed for understanding the biological profile of biothiols. In this work, we have designed and synthesized a 4'-hydroxy-[1,1'-biphenyl]-4-carbonitrile modified with NBD group-based fluorescent probe, BPN-NBD, for sensitive detection of Cys/Hcy and GSH by dual emission signals via a single-wavelength excitation. BPN-NBD exhibited an obvious blue fluorescence (λmaxem = 475 nm) upon the treatment with GSH and reacted with Cys/Hcy to give a mixed blue-green fluorescence (λmaxem = 475 nm and 545 nm). Meanwhile, BPN-NDB performed sufficient selectivity, rapid detection (150 s), high sensitivity (0.011 µM for Cys, 0.015 µM for Hcy, and 0.003 µM for GSH) and could work via a single-wavelength excitation to analytes and had ability to image of Cys/Hcy from GSH in living MCF-7 cells, tumor tissues, and zebrafish by exhibiting different fluorescence signals. Overall, this work provided a powerful tool for thiols visualization in biological and medical applications.